Trust in Philanthropy: An Examination of Multidisciplinary Factors - Mohamad Isa Abd Jalil,; Anwar Allah Pitchay,; Sofri Yahya, (Asian Academy of Management Journal, 2024)
This article explores and consolidates the factors that influence the donor’s trust from cross-disciplinary literature, and we put factors from these different fields to the test in one topic: the donor’s trust in the fundraiser organisation. Grounded on the literature, we can say that there are nine themes of constructs that influence trust. This research utilised a quantitative survey approach and PLS-SEM as an analysis platform to analyse the data collected. We have discovered that our respondents who represent donors strongly agree that their trust is heavily influenced by perceived security, rule of law, organisational personnel personality, communication effectiveness, reputation, perceived integrity, and perceived competence. Cross-disciplinary studies are profoundly helpful towards deeper knowledge and enhance the learning experience and enable the transfer of ideas across many areas of study easier. The findings should contribute to the theoretical knowledge specifically on trust antecedent in the philanthropy setting and other disciplines. The findings presented in this paper may also be useful as input for fundraisers to build and strengthen the level of their donor’s trust. This article explores and consolidates all factors that influence donor trust, which has been published in the literature and presents the results from the cross-examination of these factors.